Basic Features of Preparatory Activities in Geography Textbooks - (:unkn) unknown (MARMARA UNIV, 2016)
While organizing the educational attainment it is significant to have a good title for the educational attainment and to do preparatory work because preparatory work indicates how to precede the attainment. Preparatory work that forms the introduction that students meet firstly, should be prepared carefully because it shows what sort of knowledge will be covered and what points prioritised. In this respect preparatory works must contain a certain character. Preparatory works should have briefly; motivate students, arouse them to learn new things, make them think, make them excite to pursue the lesson, activate their old knowledge, lead to asking questions and search for the answers for these questions.
Keywords: Preparatory activities; geography textbooks; education; teaching; geography